Adverse pregnancy outcomes attributable to socioeconomic and ethnic inequalities in England: a national cohort study. Issue 10314 (20th November 2021) - Jardine, Jennifer; Walker, Kate; Gurol-Urganci, Ipek; Webster, Kirstin; Muller, Patrick; Hawdon, Jane; Khalil, Asma; Harris, Tina; van der Meulen, Jan; ,
Summary: Background: Socioeconomic deprivation and minority ethnic background are risk factors for adverse pregnancy outcomes. We aimed to quantify the magnitude of these socioeconomic and ethnic inequalities at the population level in England. Methods: In this cohort study, we used data compiled by the National Maternity and Perinatal Audit, based on birth records from maternity information systems used by 132 National Health Service hospitals in England, linked to administrative hospital data. We included women who gave birth to a singleton baby with a recorded gestation between 24 and 42 completed weeks. Terminations of pregnancy were excluded. We analysed data on stillbirth, preterm birth (<37 weeks of gestation), and fetal growth restriction (FGR; liveborn with birthweight <3rd centile by the UK definition) in England, and compared these outcomes by socioeconomic deprivation quintile and ethnic group. We calculated attributable fractions for the entire population and specific groups compared with least deprived groups or White women, both unadjusted and with adjustment for smoking, body-mass index (BMI), and other maternal risk factors. Findings: We identified 1 233 184 women with a singleton birth between April 1, 2015, and March 31, 2017, of whom 1 155 981 women were eligible and included in the analysis. 4505 (0·4%) of 1 155 981 births were stillbirths. Of 1 151 476 livebirths, 69 175 (6·0%) were preterm births and 22 679 (2·0%) were births with FGR. Risk of stillbirth was 0·3% in the least socioeconomically deprived group and 0·5% in the most deprived group (p<0·0001), risk of a preterm birth was 4·9% in the least deprived group and 7·2% in the most deprived group (p<0·0001), and risk of FGR was 1·2% in the least deprived group and 2·2% in the most deprived group (p<0·0001). Population attributable fractions indicated that 23·6% (95% CI 16·7–29·8) of stillbirths, 18·5% (16·9–20·2) of preterm births, and 31·1% (28·3–33·8) of births with FGR could be attributed to socioeconomic inequality, and these fractions were substantially reduced when adjusted for ethnic group, smoking, and BMI (11·6% for stillbirths, 11·9% for preterm births, and 16·4% for births with FGR). Risk of stillbirth ranged from 0·3% in White women to 0·7% in Black women (p<0·0001); risk of preterm birth was 6·0% in White women, 6·5% in South Asian women, and 6·6% in Black women (p<0·0001); and risk of FGR ranged from 1·4% in White women to 3·5% in South Asian women (p<0·0001). 11·7% of stillbirths (95% CI 9·8–13·5), 1·2% of preterm births (0·8–1·6), and 16·9% of FGR (16·1–17·8) could be attributed to ethnic inequality. Adjustment for socioeconomic deprivation, smoking, and BMI only had a small effect on these ethnic group attributable fractions (13·0% for stillbirths, 2·6% for preterm births, and 19·2% for births with FGR). Group-specific attributable fractions were especially high in the most socioeconomically deprived South Asian women and Black women for stillbirth (53·5% in South Asian women and 63·7% in Black women) and FGR (71·7% in South Asian women and 55·0% in Black women). Interpretation: Our results indicate that socioeconomic and ethnic inequalities were responsible for a substantial proportion of stillbirths, preterm births, and births with FGR in England. The largest inequalities were seen in Black and South Asian women in the most socioeconomically deprived quintile. Prevention should target the entire population as well as specific minority ethnic groups at high risk of adverse pregnancy outcomes, to address risk factors and wider determinants of health. Funding: Healthcare Quality Improvement Partnership.